1994
DOI: 10.1007/bf00193783
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of phase spectra by the peripheral auditory system of the bullfrog

Abstract: In this study we have examined the sensitivity of auditory nerve fibers in the bullfrog (Rana catesbeiana) to changes in the phase spectrum of an equal-amplitude multi-harmonic stimulus which spanned the bullfrog's range of hearing. To assess peripheral auditory phase sensitivity, changes in the response properties of VIIIth nerve fibers were measured when the relative phase angle of a single harmonic component nearest a unit's best excitatory frequency was systematically varied. The results revealed that shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Immobilization was maintained throughout the experiment by subsequent injections (150-300 μg) every few hours. In pilot experiments, frogs were also injected with Fentanyl (Haldid, Janssen, 1.4 nM/g; IACUC protocol AC-AAAA1277); however, additional study revealed that fentanyl has no analgesic or anesthetic effect in Xenopus (unlike in ranids; Bodnar and Capranica 1994;Stevens et al 1994;Jørgensen and Christensen-Dalsgaard 1997) and this treatment was discontinued. Thus, frogs were anesthetized only locally during recordings.…”
Section: Animals and Surgerymentioning
confidence: 99%
“…Immobilization was maintained throughout the experiment by subsequent injections (150-300 μg) every few hours. In pilot experiments, frogs were also injected with Fentanyl (Haldid, Janssen, 1.4 nM/g; IACUC protocol AC-AAAA1277); however, additional study revealed that fentanyl has no analgesic or anesthetic effect in Xenopus (unlike in ranids; Bodnar and Capranica 1994;Stevens et al 1994;Jørgensen and Christensen-Dalsgaard 1997) and this treatment was discontinued. Thus, frogs were anesthetized only locally during recordings.…”
Section: Animals and Surgerymentioning
confidence: 99%
“…Shifts in the phase spectra of multi-harmonic signals affect the degree of synchronization to the fundamental period of AP and BP fibers (Simmons et al 1993b;Bodnar and Capranica 1994a), and the spike rates of AP fibers (Bodnar and Capranica 1994a). The phase sensitivity of BP fibers and AP fibers with BEFs > 600 Hz, reflects their sensitivity to changes in the peak amplitude and envelope of the temporal waveform while the phase sensitivity of low frequency AP fibers, is at least in part, due to changes in the amplitude of difference tone distortion products which occur with shifts in the relative phase angles of the primary tones (Bodnar and Capranica 1994b).…”
Section: Effects Of Harmonic Structure On Female Preferencementioning
confidence: 99%
“…This selective coding of the waveform envelope implies that AP and BP fibers are extracting the waveform periodicity or 'pitch' of the signal. Shifts in the starting phases of the harmonics constituting complex signals produce shifts in the pattern of temporal discharges seen in the eighth nerve (Bodnar and Capranica 1994;Simmons et al 1993a). When the envelope of a synthetic advertisement call is changed by manipulations of starting phase from a prominent, impulsive-like envelope to a flatter, noiselike envelope, the precision of fundamental frequency capture declines, and more fibers phase lock to one of the lower frequency components in the signal, rather than to the waveform periodicity itself (Simmons et al 1993a).…”
Section: Introductionmentioning
confidence: 99%